Health risk assessments of arsenic and toxic heavy metal exposure in drinking water in northeast Iran - Hosein Alidadi; Seyedeh Belin Tavakoly Sany; Batoul Zarif Garaati Oftadeh; Tafaghodi Mohamad; Hosein Shamszade; Maryam Fakhari (Komiyama Printing Co. Ltd, 2019)
Abstract Background Arsenic and heavy metals are the main cause of water pollution and impact human health worldwide. Therefore, this study aims to assess the probable health risk (non-carcinogenic and carcinogenic risk) for adults and children that are exposed to arsenic and toxic heavy metals (Pb, Ni, Cr, and Hg) through ingestion and dermal contact with drinking water. Method In this study, chemical analysis and testing were conducted on 140 water samples taken from treated drinking water in Mashhad, Iran. The health risk assessments were evaluated using hazard quotient (HQ), hazard index (HI), and lifetime cancer risk (CR). Results The results of the HQ values of arsenic and heavy metals for combined pathways were below the safety level (HQ < 1) for adults, while the HI for children were higher than the safety limit in some stations. Likewise, Cr showed the highest average contribution of HItotal elements (55 to 71.2%) for adult and children population. The average values of total carcinogenic risk (TCR) through exposure to drinking water for children and adults were 1.33 × 10−4 and 7.38 × 10−5, respectively. Conclusion Overall, the CRtotal through exposure to drinking water for children and adults was borderline or higher than the safety level of US EPA risk, suggesting the probability of carcinogenic risk for the children and adults to the carcinogenic elements via ingestion and dermal routes. Therefore, appropriate purification improvement programs and control measures should be implemented to protect the health of the residents in this metropolitan city.